PREDICTION OF DIFFICULT LAPAROSCOPIC CHOLECYSTECTOMY BASED ON ULTRASONOGRAPHIC FINDINGS - PK, SHERINFARSANA; STANLEY, JOSV (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objective of the study is to the role of pre-operative ultrasonography (USG) abdomen to find difficulty in laparoscopic cholecystectomy. Methods: It was a prospective observational study conducted in the Department of General Surgery, Government Medical College, Kottayam, for a period of 12 months after obtaining approval from the Institutional Review Board and Ethical Committee. A total of 94 patients who underwent elective laparoscopic cholecystectomy were randomly allotted and their pre-operative ultrasound was assessed. Pre-operative predictability of difficult laparoscopic cholecystectomy based on USG was studied. Results: Out of 78 difficult laparoscopic cholecystectomies, 71 cases were predicted to have intra-operative difficulty with pre-operative ultrasound as per total time taken for surgery. Out of these 78 difficult cases, 68 cases were able to predict as per difficulty in dissecting GB from GB fossa. This gives a positive predictive value of 91%, which is in agreement with earlier studies. Conversion rate in our study was 9.6% of total and 11.5% of difficult cases. Those cases that were predicted pre-operatively with ultrasound to be easy were never converted to open. Conclusion: Pre-operative USG can be used as a screening method for laparoscopic cholecystectomy as this is a valuable predictor of difficulty in laparoscopic cholecystectomy in most of the cases. It will help the surgeon to make an idea of potential difficulty that he/she can face during the intra-operative period. The most valuable assessment using the ultrasound is the gall bladder wall thickness, gall bladder contracted or not, common bile duct diameter, and stones impacted in the neck of GB.